Effect of COVID-19 on immunization coverage of children aged 0-11 months in the centre region of Cameroon - Loïc D. Djommo Metchehe; Ketina H. Tchio-Nighie; Blaise Wakam Nkontchou; Lena L. Kouagnang Tchoukio; Jérôme Ateudjieu (AOSIS, 2023)
The occurrence of epidemics is known to contribute in reducing the capacity of health facilities to deliver care and the predisposition of populations to seek care through several mechanisms. The objective was to assess the effect of the COVID-19 on vaccination coverage of the expanded program of immunization (EPI) vaccines in children aged 0-11 months. The study involved a descriptive and case control designs exhaustively targeting health facilities in health areas from selected health districts. The descriptive part explored the distribution of immunization coverage 12 months before and during COVID-19. Data were extracted from monthly EPI reports of health areas. Cases were months with immunization coverages of Bacille Calmette-Guerin (BCG), Measles Mumps-Rubella 1 (MMR1) or Diphtheria-Pertussis-Tetanus Hepatitis B + Hemophilus influenzae type b dose 3 (DPT-Hi+Hb3) less than 80%. The exposure were months belonging to the pandemic period. Of the 78 targeted health areas, 74 (94.87%) were reached. The monthly immunization coverage of BCG, RR1, DPT-Hi+Hb 1 and 3 decreased during the pandemic period by minimum 30%. Being a health-area month belonging to the COVID-19 pandemic period was found to be significantly associated to lower BCG (OR=2.00 [1.61; 2.50]; p0.001), MMR1(OR=2.45 [1.76; 3.41]; p0.001) and DPT-Hi+Hb3 (OR=2.11 [1.68; 2.64]; p0.001) immunisation coverage. COVID-19 had a significant effect on the decrease of immunization coverages of antigens offered in the EPI program. This raises the need to develop interventions during health emergencies to prevent disruption of health services access.